Customer Loyalty Segmentation With Rfm Model At "ABC" Mart - Azwar, Meiriza; Azwar, Tasrika; Heikal, Jerry (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
In an effort to determine groups of customers who have the potential to be loyal, it is necessary to carry out a careful examination based on the characteristics of each customer in transactions. Having similar characteristics to create a customer grouping is also needed in the customer segmentation concept. This is necessary because it is to know customer behavior so that it can help in implementing the right sales strategy to increase profits for the company. The aim of this research is to identify customer groups using the RFM model. Based on the results of the RFM interpretation analysis carried out, 3 clusters were formed with the levels of loyal customers, less loyal customers and disloyal customers. It can be concluded that this research can group customer loyalty levels using the RFM model.